Effects of Different Types of Soil Management on Organic Carbon and Nitrogen Contents and the Stability Index of a Durum Wheat–Faba Bean Rotation under a Mediterranean Climate - Luigi Tedone; Leonardo Verdini; Giuseppe De Mastro (Agronomy, 2023)
Soil quality, nitrogen, and organic matter content are increasingly being researched due to their impact on the environment. We assessed the effects of different soil management practices on the distribution and accumulation of soil organic carbon (SOC) in a durum wheat–faba bean rotation system cultivated in a Mediterranean-type area of Southern Italy, over six years. The effects of three levels of soil disturbance—conventional tillage (CT), minimum tillage (RT), and no tillage—(NT) on the SOC and nitrogen (N) content at soil depths of 0–15, 15–30, 30–60, and 60–90 cm were compared in a long-term experiment starting in the 2009–2010 growing season. The three soil management systems showed significant differences (p < 0.05) in the surface layer (0–15 cm depth) in SOC content and total nitrogen, with the largest accumulation occurring in the conservation system (NT). In the deep layers (30–60 and 60–90 cm), however, no significant differences were found between the three tillage systems. The ascending order of the tendency to accumulate SOC and N in the soil in the 0–15 cm layer was NT > CT > RT. In addition, the C/N ratio showed a more equilibrated rate in the NT system. The conservation tillage (NT) gave the best results in terms of the physical characteristics of the soil, showing a higher stability index compared to CT and RT. Conservation tillage is therefore recommended for wheat cultivation in the dry areas of Southern Italy, due to its benefits in terms of both crop yield improvements and environmental protection.